Towards a Conceptual Model on Causal Loop Diagram - Borges, Júlia de Souza; Lahass, Thiago Felippe Neitzke; Apolinário, Amanda Brito; Barcellos, Monalessa P. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248566, 2026)
Context: Information systems are increasingly complex, shaped by interdependent technical, organizational, and human factors. Understanding this environment is crucial for developing and using information systems effectively. Systems Thinking (ST) offers tools that help in this matter. In ST, a system comprises elements and interconnections coherently organized to produce characteristic behaviors. ST tools aid in modeling complex systems and improving the understanding of their dynamics. Causal Loop Diagrams (CLDs), one of the most used ST modeling tools, represent cause-and-effect relationships and feedback structures, supporting the identification of problem causes, behavioral patterns, and enabling informed decision-making. Problem: Despite its potential, the lack of knowledge and supporting tools has limited CLD adoption. Solution: To structure knowledge about CLD, we developed a conceptual model representing its main elements, relationships, and constraints. IS Theory: This work relates to the organizational knowledge creation theory. A conceptual model provides an abstract representation of a domain, serving as a theoretical foundation that captures essential entities, their properties, and relationships. It enables knowledge formalization and supports communication among stakeholders. Method: To evaluate the model clarity and correctness, it was assessed by domain experts. To demonstrate its applicability, it was used to develop a supporting tool for CLD creation and interpretation. Results: Findings indicate that the conceptual model adequately captures essential concepts for understanding CLDs and provides structured knowledge useful for building them. The model can also serve as a reference model to aid tool development and has potential applications in semantic annotation and interoperability. Contributions and Impact to IS area: For researchers, this work advances knowledge about CLD, providing a formal representation of its conceptualization. For practitioners, it offers a model that aids in CLD understanding and communication, and in developing computational solutions. It also offers a tool to support CLD creation and interpretation, fostering its use in practice.